2015
DOI: 10.4322/rbcv.2015.321
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade microbiológica do leite cru produzido no Norte de Minas Gerais

Abstract: Objetivou-se verificar a contaminação do leite cru por micro-organismos mesófilos, psicrotróficos, coliformes a 45°C e Enterococcus spp., produzido por rebanhos mestiços, em 30 unidades agrícolas familiares produtoras de leite em Juramento e Montes Claros, na região Norte de Minas gerais. Houve quatro coletas de amostras durante um ano, sendo duas na época de chuva e duas na época da seca. Coletaram-se amostras de leite cru e cru refrigerado, observando-se a contagem total de micro-organismos mesófilos, psicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
8

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
5
0
8
Order By: Relevance
“…They hence assumed that resistant proteolytic enzymes were produced, which caused technological problems in milk and dairy products. According to MENEZES et al (2015), in the quality raw milk produced in Minas Gerais, milk samples showed high contamination by mesophilic and psychrotrophic microorganisms. These authors diagnosed that contaminations compromised the sanitary hygienic quality of milk, since the majority of the samples analyzed were not in compliance with the limits set forth by legislation either at the time of the study or presently.…”
Section: Resultsmentioning
confidence: 99%
“…They hence assumed that resistant proteolytic enzymes were produced, which caused technological problems in milk and dairy products. According to MENEZES et al (2015), in the quality raw milk produced in Minas Gerais, milk samples showed high contamination by mesophilic and psychrotrophic microorganisms. These authors diagnosed that contaminations compromised the sanitary hygienic quality of milk, since the majority of the samples analyzed were not in compliance with the limits set forth by legislation either at the time of the study or presently.…”
Section: Resultsmentioning
confidence: 99%
“…According to Menezes et al (2015), hygienic milking procedures, cleansing and disinfection of utensils and equipments are basic to avoid milk contamination by coliforms. Training of milk producers with regard to hygiene at all stages in the provision and commercialization of raw milk is mandatory to guarantee the safeness of the product for industrialization.…”
Section: Resultsmentioning
confidence: 99%
“…Although Brazilian law forbids selling of milk in natura, it is still common practice in Brazil, associated with cultural, regional and social factors (Bersot et al, 2010;Menezes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A implementação da Instrução Normativa nº 62 pelo MAPA (BRASIL, 2011) impulsionou o setor lácteo, mas, em algumas regiões do país observam-se problemas relacionados às condições higiênico-sanitárias inadequadas durante os processos de obtenção, manipulação e armazenamento do leite cru refrigerado com comprometimento da sua qualidade e inocuidade (RAMOS et al, 2014;MENEZES et al, 2015;PINTO et al, 2015;ALMEIDA et al, 2016). Além disso, ainda são detectados resíduos de antibióticos em leite o que acarreta problemas à saúde dos consumidores (NERO et al, 2007;RODRIGUES et al, 2012 (IDAF, 2013).…”
Section: Introductionunclassified